2012
DOI: 10.1093/chromsci/bms044
|View full text |Cite
|
Sign up to set email alerts
|

An Isocratic HPLC Method for the Determination of Sorbitol and Glycerol in Pharmaceutical Formulations

Abstract: Sorbitol and glycerol, along with other inactive ingredients such as preservatives and dyes, are commonly used in various pharmaceutical and personal care products. To accurately assess the effectiveness of various formulations containing sorbitol and/or glycerol, their quantitative determination is essential. In the current study, two types of detectors (a Varian evaporative light scattering detector and an Agilent ultraviolet-visible detector) are evaluated for the assay of working sample solutions. The two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…These peaks confirm the presence of alkenes with terminal and non-terminal double bonds as well as alkanes. These results are basically consistent with the results reported by other researchers [10][11][12][13]. The FTIR spectrum of the bio-hydrocarbons produced by deiodizing 2-iodohexane by gas phase pyrolysis at 260 °C for 45 minutes are shown in Figure 8.…”
Section: -Iodohexane De-iodizationsupporting
confidence: 91%
See 1 more Smart Citation
“…These peaks confirm the presence of alkenes with terminal and non-terminal double bonds as well as alkanes. These results are basically consistent with the results reported by other researchers [10][11][12][13]. The FTIR spectrum of the bio-hydrocarbons produced by deiodizing 2-iodohexane by gas phase pyrolysis at 260 °C for 45 minutes are shown in Figure 8.…”
Section: -Iodohexane De-iodizationsupporting
confidence: 91%
“…Sulfuric acid (H2SO4) solution 0.005 N was used as the mobile phase. The flow rate of the mobile phase was maintained at 0.6 mL/min by the column temperature at 65 °C [13]. A relative index detector was attached to measure what amount of each compound passed the detector during a certain retention time.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The ingredients of the hydrogel were adjusted to have the viscosity and feel of toothpaste. CMC, numerous hydroxyl and carboxylic groups and sorbitol and glycerol, which are all known humectants, all have the ability to retain water and so affect viscosity [29,30]. Presently, the concentrations of these materials were fixed and that it was observed that the increase in HAp concentration progressively increased caused the viscosity of the fabricated hydrogels.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, HPLC has been combined with many sensitive detection techniques and has experienced continuous improvement of stationary phases, which have improved its sensitivity and specificity. HPLC is currently widely used for the analysis of drugs and dosage forms with respect to quality control, quantitative determination of active ingredients and impurities, monitoring drug blood concentration in patients, and bioequivalence assessment [10][11][12].…”
Section: Hplc Methodmentioning
confidence: 99%